Numerical Evaluation of the Opening Effects on the Reinforced Concrete Slab Structural Performance - Meysam Aminitabar; Omar Kanaani; Amir Reza Eskenati (Shock and Vibration)
A finite element method was used in this study to investigate the effects of openings on the resistive behavior of concrete slabs. The presented modeling procedure is used to conduct numerical analyses on the response of reinforced concrete slab subjected to in-plane monotonic loads in X (perpendicular to the beam) and Z (parallel to the beam) directions. Initially, the developed numerical model was calibrated and compared with laboratory results. In building this three-dimensional model, it is attempted to accurately model all nonlinear properties of steel and concrete materials as well as the interactions between them. Then, the behavior of bilaterally concrete slabs under different loads was investigated and used as a reference. Finally, the effect of openings under different loads on the strength of concrete slabs was studied. The results confirm that openings have a great influence on the change of hardness, ductility, initiation and cracking path, and stress distribution under shear and gravitational loading. Moreover, by adding an opening inside the diaphragm, not only did beam and block flooring show more fragile behavior, but also its strength and resistance decreased against lateral load. Given the results of the parametric study of the effect of layout, generally, its place became critical at the state that opening disturbed transmission of shear stresses to the collector beams. By adding the area of the opening and loading in X direction, the concentration of the tensile stresses (equivalent to main maximum stresses) was at the tensile edge as well as at the middle of the flooring around the opening. It is worth noting that an increase in the opening’s area caused the number of tensile stresses to be increased at the middle of the flooring. Meanwhile, the concentration of maximum compressive stresses which is equivalent to the main minimum stresses was at the compressive edge, started at the area of the collectors, and stretched to the edge of the opening. Among different layouts, X-1 and Z-3 states were more critical than other states. Considering openings with different layouts, X-1 and Z-3 have the most stiffness deteriorating and strength in such a way that stiffness deteriorating and strength were 39.93% and 37.89%, respectively, for Z-3 model and 38.68% and 43.33%, respectively, for Z-3 model.